Catalysts and motivations for change in privacy coordination: transracial, internationally adoptive parents' coordination of private, adoption-related information. Issue 1 (1st January 2021) - Loftus, Mary Claire Morr; Suter, Elizabeth A.; Strasser, Daniel S.; Hanna, Michele D.
ABSTRACT: Communication Privacy Management theory (CPM) was applied in a qualitative analysis of survey responses from parents in transracial, internationally adoptive families concerning their management of private, adoption-related information. Participants were 166 parents of at least one child adopted from China or Vietnam who responded to an open-ended online questionnaire. Most parents described at least one change in coordination of their child's private, adoption-related information over time. Of the catalysts that prompted these changes, 43% were due to the child's development, 30% to the parent's lived experiences, and 15% to privacy turbulence. Parents reported a variety of motivations for privacy management before and after these changes. Expressive need represented 64% of the pre-change motivations. Control (45%) and preventing hurt (36%) represented the predominant post-change motivations. Significant to CPM, these accounts show parents acting as proxy owners for their young children and demonstrate developmental changes in privacy management within families.